Utilizing CaCO3, CaF2, SiO2, and TiO2 phosphors as approaches to the improved color uniformity and lumen efficacy of WLEDs - Huu Phuc Dang; Phung Ton That; Nguyen Doan Quoc Anh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
The two elements that are most favorable in the quality evaluation for phosphor-converted LEDs (pcLEDs) these days are the chromatic homogeneity and the lumen output. In this study, a thorough research on enhancing color uniformity and luminous flux of pcLEDs that have a high correlated color temperature (CCT) of 8500K is carried out. The scattering enhancement particles (SEPs): CaCO3, CaF2, SiO2, and TiO2 are used to accomplish the goal by adding them to a yellow phosphor compounding Y3Al5O12:Ce3+, and comparing their characteristics afterwards. LightTools program is used to build an optical simulation and Mie-scattering theory helps to examine the achieved results. Specifically, the parameters included in SEPs’ scattering calculation are the scattering coefficients, the anisotropic scattering, the reduced scattering, and the scattering amplitudes at 455 nm and 595 nm. The outcomes presented that compared to other SEPs, TiO2 particles can yield the highest chromatic homogeneity. However, the lumen output reduces considerably as TiO2 concentration greatly increases while it can be bettered when using SiO2 particles with any particle size. For CaCO3 particles, the color deviation of 620 K CCT can be reduced with 30% concentration, leading to the recommendation of using CaCO3 to promote the CCT homogeneity and luminescence efficiency.